Species of Dirhinus Dalman, 1818 (Hymenoptera: Chalcididae, Dirhininae) from Saudi Arabia: new species and a new record - Gul, Muhammad Athar; Soliman, Ahmed M.; Dhafer, Hathal M. Al; Gadallah, Neveen S. (Zootaxa, 2018)
The species of chalcidid wasps of Dirhinus Dalman, 1818 (Hymenoptera: Chalcididae) from Saudi Arabia are reviewed. Seven species are reported from Al Bahah, Asir, Jazan and Riyadh regions, of which three have hitherto been recorded: D. (Dirhinus) anthracia Walker, 1846, D. (Dirhinus) himalayanus Westwood, 1836 and D. (Dirhinus) wohlfahrtiae Ferrière, 1935. One species D. (Dirhinus) claviger Bouček & Narendran, 1981 is recorded for the first time from Saudi Arabia (Asir). Additionally, three new species: D. (Dirhinus) asirensis sp. nov. (Asir), D. (Dirhinus) sculpturatus sp. nov. (Al Bahah, Asir and Riyadh) and D. (Pareniaca) transversus sp. nov. (Al Bahah, Asir and Jazan) are described and illustrated. An illustrated key to females of the species of Dirhinus from Saudi Arabia is provided.